Constructing an Achievement Reference Test to measure language competencies – A descriptive survey study on secondary school students in Riyadh City – - ALAssiri, Ibrahim Zaid; Al-Zahrani, Muhammad Rizkallah (Journal of Educational and Psychological Sciences, 2020)
The present study aims to build a criterion- reference test to measure linguistic competencies of secondary school students in Riyadh, and to verify its psychometric characteristics. The descriptive survey method was used as it is the appropriate method to achieve the objectives of the study. Further, the sample of the study consists of (50769) students, representing all secondary students in Riyadh between 1439/1440 AH in accordance with the data obtained by the researcher. Also, the population of the current study consists of (983) secondary students in Riyadh as a sample. The researcher built the test in four stages: (analysis stage- construction phase- experimentation stage- output stage). After passing these steps to build the test, the study produced a criterion-reference test to measure the linguistic competencies for the secondary school students which consist of (40) questions measuring two linguistic competencies (syntactic and dictation competency).The study found that this test has good validity and it was found that the test has high reliability according to Livingstone coefficient to the degree of (85%). Based on these results, the study recommends that the application of the test built in the current study is appropriate to measure students’ linguistic competencies. This study also recommends that the measurement and evaluation experts should find new ways to build tests based on criterion-reference in all subjects of education.
Keywords: Achievement test; criterion; reference test; linguistic competencies; secondary school; Riyadh